Republic at risk : an introduction to American politics - Stone, Walter J.; McCann, James A. (Cambridge : Cambridge University Press, 2022)
When people have the freedom to further their own personal interests in politics, the results may be disastrous. Chaos? Tyranny? Can a political system be set up to avoid these pitfalls, while still granting citizens and politicians the freedom to pursue their interests? Republic at Risk is a concise and engaging introduction to American politics. The guiding theme is the problem of self-interest in politics, which James Madison took as his starting point in his defense of representative government in Federalist 10 and 51. Madison believed that unchecked self-interest in politics was a risk to a well-ordered and free society. But he also held that political institutions could be designed to harness self-interest for the greater good. Putting Madison's theory to the test, the authors examine modern challenges to the integrity and effectiveness of US policy-making institutions, inviting readers to determine how best to respond to these risks.
Title from publisher's bibliographic system (viewed on 17 May 2021).
Keywords: elektronické knihy; electronic books; Pressure groups -- United States; Representative government and representation -- United States; Political participation -- United States; Elections -- United States